The Effect Of Smart Growth Principles on Affordable Housing - Abbas, Sanaa Sati; Abdulmaged, Tamara Mutaz (Iraqi Journal of Architecture and Planning, 2018)
The concept affordable housing deals with affording adequate housing to a moderate and low income households. The research defined affordable housing as housing deals with moderate and low income households (60%-80% AMI) that housing costs donâ€™t exceed (30%) of their annual income (renting or owning) , while smart growth is defined as a development that contains a set of principles related to compact design and affordable housing .The research problem is embodied as (a knowledge gap about the effects of smart growth principles at a micro scale on the costs of affordable housing).The research built a theoretical framework including both of affordable housing and smart growth concepts. It included two terms, the first one was the ( smart growth principals) , and the second one was ( the smart growth at a micro scale (community)). The measurement included indicators driven from the theoretical framework, which had been applied on three national, Arabic and local projects. Finally the research finding showed different results varied between the different projects and the most effective principal was (affordable housing choices). Key words: Smart Growth , Affordable Housing , Compact Smart Growth development, Smart Growth development scale. Â